PHYSICAL ACTIVITIES OF SOUTH KALIMANTAN PRIMARY SCHOOL STUDENTS OUTSIDE SCHOOL HOURS - Dirgontoro, Edwin Wahyu; Amirudin, Akhmad; Fauzan, Lazuardy Akbar; Hayati, Nor; Adawiyyah, Sa'wadzatul (Riyadhoh : Jurnal Pendidikan Olahraga, 2023)
The aim of physical education is to develop physical abilities. Good physical abilities have an impact on students' ability to think and concentrate on learning. Children aged 5 to 17 years are recommended to do physical activity with a duration of 60 minutes in the moderate to vigorous intensity category. Physical activity done more than 60 minutes a day can provide body health. Learning PE at school, all the time available for learning is not fully used effectively so that to gain physical fitness students must spend time doing physical activities outside of learning hours. The aim of this research is to determine the physical activity carried out by students outside school hours. The sample for this research was 174 students in elementary schools throughout South Kalimantan. This research uses quantitative descriptive research methods. The technique used in taking samples is purposive sampling. The instrument used to obtain research data was the IPAQ questionnaire. The research results showed that physical activity carried out by students with heavy activities was mostly carried out for 3 days with a percentage of 28%, the time range used was 60-90 minutes a day. Students who do moderate activities mostly do it for 2 days with a percentage of 24%, the time span used is less than 60 minutes a day. Students' walking activities are mostly carried out for 7 days with a percentage of 61%, the time range used is 60-90 minutes a day. Students do most of the sitting activities for 7 days with a percentage of 59%, the time range used is 60-90 minutes a day. Elementary school students do a lot of physical activity in the moderate category with a range of 600 – 6000 MET-minutes/week as much as 51.72%.